« Alzarse » : les formes d’une pratique, depuis l’époque des palenques jusqu’à l’extinction des derniers groupes de guérilleros anticastristes - Vincent Bloch (Centre de Recherches sur les Mondes Américains, 2008)
This article hinges upon historical analysis to describe the complexity of the alzamientos ("uprisings") that took place in Cuba between 1959 and 1965 by reflecting on the way in which they intermingled practices anchored in long-term local history, registers of political action belonging to the "system of competitors for power share" with a sequence of events that had confrontations shift towards an ideological ground first, then towards phantasmagorical representations.